Modelagem hidrológica aplicada ao estudo da vazão da bacia hidrográfica do rio Araguari - MG, a partir das mudanças do uso da terra e cobertura vegetal nativa - Silva, Mirna Karla Amorim da (2014)
The Araguari river hydrographic basin (BHRA) presents an area of 22,146.23 km2 and is located in a region of Minas Gerais State with high water demand by agriculture, industry and humans, which leads to high environmental costs, including damage of natural water resources systems. The frequent land use changes related to such activities often degrade water resources and therefore should be monitored in order to provide effective environmental management strategies, consistent with conservation activities of existing water streams. In this context, considering the need of efficient water resources management programs, the hydrological modeling becomes an important tool to help monitoring and management activities of water resources found in the watershed. Among numerous hydrological models, we can highlight (as used in this research) the ones having functions to overcome the demand for reliable and continuous data sets. In other words, these models can overcome situations where there is total or partial lack of data collected by hydrometeorological stations and even simulate situations/hypothetical scenarios for verification of some phenomena, for example, the behavior of stream flows. Thus, the objective of this research is to use a hydrological modeling to study the stream flow of BHRA, considering changes in land use and natural vegetation. The selected hydrological model was the Modelo de Grandes Bacias (MGB), developed by Instituto de Pesquisas Hidráulicas (IPH) from the Federal University of Rio Grande do Sul (UFRGS). The effects of land use and land cover (LULC) changes (time period of 1975-2010) in the stream flow regime were evaluated. The main LULC changes in the study area in this time period was the replacement of natural grasslands (Campo limpo, Campo sujo and Campo Cerrado) by croplands and cultivated pasturelands, as result of great increase of economic activities in this region. In 2010, the natural vegetation was reduced to nearly half of found in 1975 (88,93% and 42,97% of basin covered by natural vegetation in 1975 and 2010, respectively). Cultivated pasturelands increased from 8,41% in 1975 to 30,59% in 2010. Croplands increased from 2% in 1975 to 23,02% in 2010. The MGB was adjusted to simulate daily stream flows of the BHRA based on rainfall, climate and stream flow data gathered by eight rain gauged stations, 54 rainfall stations, besides the following spatial data: digital elevation models derived from the Shuttle Radar Topography Mission (SRTM); soil, geomorphology, geology and two-year LULC map (1975 and 2010). The calibration and simulation of MGB for BHRA showed good fit between observed (ANA) and calculated stream flow (MGB). The BHRA was then divided into sub-basins for further analysis. The Ibiá sub-basin showed better results of calibration and simulation of daily stream flows. The stream flows of Fazenda São Mateus, Desemboque and Fazenda Letreiro sub-basins were also analyzed. The Fazenda Letreiro sub-basin, the one that presented highest levels of LULC changes in the time period considered (conversion of 53,56% of natural vegetation into croplands and cultivated pasturelands) showed an increase of maximum (38,8 m3/s), minimum (2,29 m3/s) and average (5,78 m3/s) stream flow and for annual laminar flow (231,35 mm/year) as well. Hypothetical scenarios were simulated for the Ibiá sub-basin and compared with the stream flow results estimated by MGB for the year 2010. For actual LULC conditions, the measured and the estimated mean stream flows were quite similar. In a scenario of 100% of natural vegetation cover, the minimum stream flow increased 2,28 m3/s. In a scenario of 100% of cultivated pasture, the maximum stream flow presented highest increase of 36,18 m3/s. The use of the model and the analyses conducted in this study were considered satisfactory to meet the proposed research objectives.